Introduction to the special issue on communication technologies and relationships. (December 2021) - Perlman, Daniel; Sprecher, Susan; Drouin, Michelle
This introduction to a special Technology and Relationships issue of the Journal of Social and Personal Relationships introduces the collection of articles. It describes the editorial development of the issue, identifies how the articles are organized into three clusters reflecting the developmental arc of relationships, provides a precis of each article, and ends with reflections on a question (is technology beneficial or detrimental?) and two noteworthy aspects of the collection (theory and methodology).